KOALISI DALAM SISTEM DEMOKRASI PRESIDENSIAL INDONESIA : Faktor faktor Kerapuhan Koalisi Era Presiden Yudhoyono - Haris, Syamsuddin (Jurnal Penelitian Politik, 2025)
Although the concept ofcoalition is only prevalent in parliamentary democratic system but multiparty pre sidential system scheme which is applied in Indonesia necessitates the existence ofcoalition among its party The presence of Coalition is necessary to minimize the risk ofpolitical deadlock in relations between President and Parliament on the one hand and due to built effectiveness in the government as the outcome ofgeneral election But in fact political coalition do not guarantee effectiveness in government administration even on the contrary it has become a prison for president because opposition comes from inside of The Parliament which also part of the coalition member in government In the era ofPresident Yudhoyono there are three importantfactors that lead to fragility of the coalition the coalition design factor personalityfactor of the President and character of the party in theparliament In order to Built effectiveness in government which requires restructuring the coalition form especially related to coalition base political nature of the agreement and contract among the members of coalition scope ofmaterial agreement and internal mechanism in the coalition in thefuture the effectiveness is also going to be base on restructuring general election format to become national general election to elect Pre sident and Vice President and members ofparliament and local elections to choose head oflocal government province and district and members of local house of representatives)